The Europeans' expectations of competition effects in passenger rail transport: a cross-national multilevel analysis - Dias, J. G.; Trindade, G. (Social Indicators Research, 2016)
This study explores the overall expectations of Europeans on railway competition effects for long-distance passenger transport. This construct is measured by a set of items, namely how railway companies are managed, frequency of trains, ticket prices, quality of services offered to passengers on the train, punctuality, number of stations or routes served, safety of the railway network, and comfort and cleanliness of trains. A multilevel factor framework controls within- and between-variability across European Union countries and takes cross-country invariance into account. Results show that the overall expectations of Europeans on railway competition effects are significant in explaining variations in all the observed items for the railway competition effects at both levels. The multilevel structure (between-country variability) accounts for 12.1 % of the total variability.